Authentizität und industriekulturelles Erbe Zugänge und Beispiele - Farrenkopf, Michael; Meyer, Torsten (Veröffentlichungen aus dem Deutschen Bergbau-Museum Bochum, 2020)
This volume examines commemorative cultures and sites, processes of authenticating industrial heritage, as well as the spatial dimensions of commemorative sites in a European and international comparison. It places a focus on former mining districts.